Induced drought in an Amazonian forest affects diversity but not foraging distance of generalist ants - Almeida, Rony P. S.; Baccaro, Fabrício B.; Ellison, Aaron M.; Camarota, Flávio; Silva, Rogério R. (Ecological entomology, 2025)
Ongoing environmental change is forecast to lead to lower precipitation and concomitant species losses in tropical regions. These losses may affect generalist species that provide essential ecosystem services, such as controlling the rate at which nutrients become available for uptake by other organisms in tropical forests. Here, we use a long‐term (16 years) rainwater exclusion experiment in a primary Amazonian tropical rainforest (Caxiaunã National Forest, Northern Brazil) to test whether induced water stress (“drought”) affects the species richness of generalist ants, their abundance (i.e., nest density), and the distance at which they detect food resources (i.e., baits). The number of generalist ant species and colonies was reduced by 50% in the drought‐induced plot, and ant species composition differed between the control (typical moist forest) and drought‐induced plots. Although ants that nested in both control and drought plots had shorter estimated foraging distances than habitat specialists, the distance at which these colonies detected baits was not affected by drought. We conclude that the extremely high diversity of tropical forest ants may be able to buffer the detrimental effects of drought on the resource detection rates of generalist ants. Different generalist ant species were also functionally similar to wet‐forest species that cannot forage under drier conditions. The number of ant species and colonies was reduced by 50% in the drought‐induced plot, compared to the typical moist forest. Ants that nested in both the control (moist forest) and drought‐induced plots had shorter estimated foraging distances than habitat specialists. The distance at which generalist ant species detected baits was not affected by drought.